The Encyclopedia of Clinical Psychology 2015
DOI: 10.1002/9781118625392.wbecp284
|View full text |Cite
|
Sign up to set email alerts
|

Personality Assessment Inventory ( PAI )

Abstract: The Personality Assessment Inventory ( PAI ) is a multiscale personality inventory that measures a variety of constructs relevant to clinical diagnosis and decision making. The PAI is a questionnaire that has 344 self‐reported items arranged into 22 full scales, with various subscales and supplemental indices available to refine interpretation. First published in 1991, the PAI was developed using a construct‐validation approach that sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
249
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(255 citation statements)
references
References 13 publications
4
249
1
1
Order By: Relevance
“…The mTBI + PCS group was recruited first and the HC group was matched to the clinical group on demographic characteristics of age, education, and gender. 31,32 mTBI was defined by standard diagnostic criteria to include a loss or altered state of consciousness for less than 15 min postinjury or a period of post-traumatic amnesia of less than 24 h or a Glasgow Coma Scale rating between 13 and 15. 33,34 As part of the exclusion criteria, all participants underwent a structural MRI (1.5T GE scanner; GE Healthcare, Woburn, MA) with a standardized TBI sequence, including a sagittal magnetization-prepared rapid acquisition gradient echo, axial gradient-echo T2*, axial fluid-attenuated inversion recovery, axial T2, and axial diffusion-weighted imaging (DWI).…”
Section: Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The mTBI + PCS group was recruited first and the HC group was matched to the clinical group on demographic characteristics of age, education, and gender. 31,32 mTBI was defined by standard diagnostic criteria to include a loss or altered state of consciousness for less than 15 min postinjury or a period of post-traumatic amnesia of less than 24 h or a Glasgow Coma Scale rating between 13 and 15. 33,34 As part of the exclusion criteria, all participants underwent a structural MRI (1.5T GE scanner; GE Healthcare, Woburn, MA) with a standardized TBI sequence, including a sagittal magnetization-prepared rapid acquisition gradient echo, axial gradient-echo T2*, axial fluid-attenuated inversion recovery, axial T2, and axial diffusion-weighted imaging (DWI).…”
Section: Recruitmentmentioning
confidence: 99%
“…31 The Personality Assessment Inventory (PAI) was administered as a measure of psychiatric functioning. 32 As there are potential effects of co-occurring post traumatic stress disorder on cognitive tests, the PAI ARD-T t-score was included as a potential covariate. 32 The California Verbal Learning Test (CVLT-II) and the Brief Visuospatial Memory Test (BVMT-R) were included as measures of verbal and visual learning and memory.…”
Section: Neuropsychological Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical rating scales designed to assess psychopathy have been used in taxometric research, including various versions of the Psychopathology Checklist (PCL) and its revisions, the PCL-Revised and the PCL-Antisocial Process Screening Device (Frick and Hare, 2001;Hare 1993), antisocial subscales of the Personality Assessment Interview (Morey, 2007), and the Levenson Self-Report Psychopathology Scale (Levenson et al, 1995). Within this tradition, eight studies conducted among adult jail and/or prison inmates (Dana, 1990;Edens et al, 2006;Guay et al, 2007;Marcus et al, 2004;Walters, 2009;Walters et al, 2007aWalters et al, , 2007bWalters et al, , 2007cWalters et al, , 2008 and two studies (Edens et al, 2011;Murrie et al, 2007) conducted among adolescents in juvenile correctional facilities consistently yielded evidence of dimensionality of psychopathy.…”
mentioning
confidence: 99%
“…The NSI is a part of the Comprehensive TBI Evaluation that is administered to every Veteran in Department of Veterans Affairs (VA) clinical settings who screen positive for TBI and opt for further evaluation of their symptoms. Vanderploeg et al [23] identified items on the NSI that were most highly correlated with the mild Brain Injury Atypical Symptoms scale (mBIAS) [25] and the Negative Impression Management scale on the Personality Assessment Inventory (PAI) [26] to create the Negative Impression Management Atypical Scale (NIM5), which contained highly unlikely or bizarre symptoms. They then identified the least frequently endorsed NSI items across various mild to severe TBI clinical and nonclinical samples to create the NSI Infrequent Scale (LOW6).…”
Section: Introductionmentioning
confidence: 99%